Eight-element flexible MIMO antenna based on characteristics mode theory with enhanced channel capacity for sub 6 GHz 5G communications - Deepthi Mariam John; Shweta Vincent; Sameena Pathan; Kunjan D Shinde; B S Supreetha; Tanweer Ali (Results in Engineering)
The rapid progress in wireless technology introduces a suite of furtherance designed to fulfil the ever-growing data consumption, expansion of smart devices, and rise of the Internet of Things (IoT). Such hyper-connected communication demands multiple input multiple output (MIMO) systems to meet the channel capacity. The modeling and analysis of an eight-element MIMO antenna for 5G wireless communication is communicated in the article. The single-element antenna constitutes a co-planar waveguide (CPW) fed transformed circular monopole antenna designed using the theory of characteristic modes (CMA) to cover the specific band. The proposed eight-element antenna has progressively evolved by placing the dual-element orthogonal to each other. The antenna possesses a total dimension of 1.76λ × 1.76λ × 0.0013 λ (λ computed corresponding to the lower frequency of 3.92 GHz) and offers an impedance bandwidth of 25.20 % (3.92–5.05 GHz). The orthogonal orientation and a connected ground structure offer 21 dB isolation over the bandwidth. Further, the antenna is estimated using conformal and on-body analysis for wearable application scenarios. The antenna exhibits an excellent bending profile and low specific absorption rate (SAR) value, suitable for wearable applications. The MIMO performances show excellent results with favourable MIMO metrics and a channel capacity of 42.46 bps/Hz suited for seamless communication. The link budget estimation in a line-of-sight (LOS) scenario is presented in the article to understand the integration of the antenna in the real-time communication domain.